A European Survey on Digestive Perianastomotic Ulcerations, a Rare Crohn-like Disorder Occurring in Children and Young Adults. Issue 3 (September 2021) - Madre, Chrystele; Mašić, Mario; Prlenda-Touilleux, Daniela; Brueckner, Annecarin; Koletzko, Sibylle; Fabre, Alexandre; Viala, Jérome; Lima, Rosa; Enaud, Raphael; Lemale, Julie; Kolho, Kaija-Leena; Bergoin, Charlotte; et al.
ABSTRACT: Objectives: Digestive perianastomotic ulcerations (DPAU) resembling Crohn disease lesions are long-term complications of intestinal resections, occurring in children and young adults. They are known to be uncommon, severe and difficult to treat. Methods: In the absence of recommendations, we performed a large European survey among the members of the ESPGHAN working group on inflammatory bowel disease (IBD) in order to collect the experience of expert pediatric gastroenterologists on DPAU. Results: Fifty-one patients (29 boys and 22 girls) were identified from 19 centers in 8 countries. Most patients were followed after necrotizing enterocolitis (n = 20) or Hirschsprung disease (n = 11). The anastomosis was performed at a median age (interquartile range) of 6 [1–23] months, and first symptoms occurred 39 [22–106] months after surgery. Anemia was the most prevalent symptom followed by diarrhea, abdominal pain, bloating, and failure to thrive. Hypoalbuminemia, elevated CRP, and fecal calprotectin were common. Deep ulcerations were found in 59% of patients usually proximally to the anastomosis (68%). During a median follow-up of 40 [19–67] months, treatments reported to be the most effective included exclusive enteral nutrition (31/35, 88%), redo anastomosis (18/22, 82%), and alternate antibiotic treatment (37/64, 58%). Conclusions: Unfortunately, persistence of symptoms, failure to thrive, and abnormal laboratory tests at last follow-up in most of patients show the burden of DPAU lacking optimal therapy and incomplete understanding of the pathophysiology.